piR-hsa-211106 Inhibits the Progression of Lung Adenocarcinoma Through Pyruvate Carboxylase and Enhances Chemotherapy Sensitivity - Liu, Yongmei; Dong, Yanhan; He, Xinjia; Gong, Anjing; Gao, Jinning; Hao, Xiaodan; Wang, Shuai; Fan, Yuqiao; Wang, Zibo; Li, Meng; Xu, Wenhua (Frontiers in Oncology, 2021)
Although the importance of PIWI-interacting RNAs (piRNAs) in cancer has recently been recognized, studies on the role and functional mechanism of piRNAs in lung adenocarcinoma (LUAD) development and progression are limited. In this study, we identified 10 differently expressed piRNAs in LUAD tissues compared to normal tissues, among which, piR-hsa-211106 expression levels were downregulated in LUAD tissues and cell lines. Furthermore, the effects of piR-hsa-211106 on the malignant phenotypes and chemosensitivity of LUAD cells were detected by gain- and loss-of-function analysis in vitro and in vivo, which showed that piR-hsa-211106 inhibited LUAD cell proliferation, tumor growth, and migration, but promoted apoptosis. Moreover, our finding indicated that piR-hsa-211106 is a potential therapeutic target that synergistically imparts anticancer effects with a chemotherapeutic agent for LUAD - cisplatin. Further mechanistic investigation indicated that piR-hsa-211106 could bind to pyruvate carboxylase (PC) by RNA pull down and RNA immunoprecipitation assays and inhibited PC mRNA and protein expression. Our study demonstrates that piR-hsa-211106 inhibits LUAD progression by hindering the expression and function of PC and enhances chemotherapy sensitivity, suggesting that piR-hsa-211106 is a novel diagnostic and therapeutic target for LUAD.